Optimization of Cluster House Construction Using Critical Path Method (CPM) and Evaluation and Review Technique (PERT) Program at PT.XYZ - Hedi Saepudin, Tubagus; Turseno, Andi; Tri Panudju, Andreas; Masrida, Reni; Ramadhan, Riyan (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
PT.XYZ So research was carried out so that we could find the critical path for a house construction project using the CPM method, the duration of the critical path for building a house, and how much budget was spent on building a house using the CPM method. CPM is a project management concept which is interpreted in a network image that marks project activities from start to finish with the aim of determining the critical path and PERT is a network model that is able to determine the completion time of activities. The aim is to assess and review development projects and requires three calculations. optimistic, pessimistic and realistic. The results of this research show that house construction project work using the CPM method has a work duration of 182 days, a decrease of 118 days from the actual duration and the costs incurred in this work are IDR 1,956,043,000. can reduce the budget by IDR 771,914,000/35% of the actual budget. The house construction project produces a Te value of 182.48 and a standard deviation value of 8.09 and has a probability of 53.59% if the project is completed within 182 days. However, if you use the assumption that the project can be completed within 190 days, the probability is 83.89%.